2004
DOI: 10.1002/bip.20007
|View full text |Cite
|
Sign up to set email alerts
|

Invasive cleavage reactions on DNA‐modified diamond surfaces

Abstract: Recently developed DNA-modified diamond surfaces exhibit excellent chemical stability to high-temperature incubations in biological buffers. The stability of these surfaces is substantially greater than that of gold or silicon surfaces, using similar surface attachment chemistry. The DNA molecules attached to the diamond surfaces are accessible to enzymes and can be modified in surface enzymatic reactions. An important application of these surfaces is for surface invasive cleavage reactions, in which target DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 36 publications
0
53
0
Order By: Relevance
“…The high chemical stability of diamond has been demonstrated previously when covalently linked to DNA oligonucleotides (22,32) and when functionalized with EG oligomers for protein resistance (40). However, no previous study has examined stability of proteins covalently linked to diamond surfaces.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The high chemical stability of diamond has been demonstrated previously when covalently linked to DNA oligonucleotides (22,32) and when functionalized with EG oligomers for protein resistance (40). However, no previous study has examined stability of proteins covalently linked to diamond surfaces.…”
Section: Resultsmentioning
confidence: 95%
“…While the surface chemistry of carbon is relatively unexplored, in recent work we have shown that photochemical grafting of organic alkenes can provide an extremely robust way to link functional organic molecules to surfaces of carbon, including diamond (22)(23)(24)(25)(26), amorphous carbon (23,27,28), glassy carbon (29), and carbon nanofibers (30,31). Carbon surfaces functionalized in this manner have shown excellent stability, even at elevated temperatures (32). Of the various forms of carbon, diamond and diamond-like carbon (DLC) are of particular interest because diamond's unique role as the hardest natural material makes it of interest for possible application as a thin-film coating material for biomedical implants such as prosthetic devices.…”
mentioning
confidence: 99%
“…Recently, we showed that diamond thin films functionalized with biomolecules such as DNA and proteins exhibited extremely good stability [8,12,19], even at elevated temperatures [20]. Moreover, we showed that it was possible to directly detect the changes in charge distribution associated with surface binding events via impedance measurements [19] and in field effect devices [8,21].…”
Section: Introductionmentioning
confidence: 96%
“…-apoobelin ) -aflatoxin B1 (AfB1) ) -DNA (Fu et al 2007) -luciferase Puzyr' et al 2004) -Alpha-bungarotoxin (Liu et al 2008 (Miller and Brown 1996;Knickerbocker et al 2003;Lu et al 2004;Strother et al 2002;Yang et al 2002;Takahashi et al 2003;Yeap et al 2008;Zhang et al 2009b;Zheng et al 2009;Chang et al 2010) (Strother et al 2002;Takahashi et al 2003;Ida et al 2003;Tsubota et al 2003;Härtl et al 2004;Christiaens et al 2006;Chang et al 2010) (Liu et al 2004;Ando et al 1996b;Khabashesku et al 2005;Ando et al 1996a;Ando et al 1993) (Ando et al 1996a;Ikeda et al 1998;Takahashi et al 2003;Miller and Brown 1996) Silanes Aryl Alkyl Amino (Zhang et al 2009b;Liang et al 2009;Krüger et al 2006;Yeap et al 2008 Zheng et al 2009) choice of biological buffer systems or media is also important, since both foetal bovine serum and phosphate buffered saline, two common biological buffer systems, tend to cause re-aggregation (Neugart et al 2007;Vaijayanthimala et al 2009). Despite the challenges involved in preparing and maintaining de-aggregated nanodiamonds, positive results strongly support their use in biological applications.…”
Section: Oxidation/carboxylation Reductionmentioning
confidence: 99%
“…In one study, the application of nanodiamonds to the skin of mice did not cause contact hypersensitivity or other allergic reactions (Burleson et al 2009). At a dose of 1mg/kg, Other -DNA (Christiaens et al 2006;Takahashi et al 2003;Knickerbocker et al 2003;Lu et al 2004;Rezek et al 2006;Yang et al 2002) -DNA (Ushizawa et al 2002) (ester linkage) Table 6 Cells showing good biocompatibility with nanodiamond in vitro HeLa cells (human cervical carcinoma) (Faklaris et al 2008;Vaijayanthimala et al 2009) Human lung adenocarcinoma cells Liu et al 2007;Liu et al 2009) Keratinocytes (Burleson et al 2009;Schrand et al 2007) Neuroblastomas (Schrand et al 2007) PC-12 cells (Schrand et al 2007) Lung fibroblasts Embryonic fibroblasts Vaijayanthimala et al 2009) Human kidney cells Osteoprogenitor cells (Vaijayanthimala et al 2009) Macrophages (Schrand et al 2007) 4 nm nanodiamonds instilled into the mouse trachea were phagocytosed by alveolar macrophages within 24 h, with a decrease in the number of nanodiamonds observed in the alveolar area throughout the study. Histopathological and ultrastructural investigations at 7, 14 and 28 days postexposure also showed no adverse effects in the lungs; nor did nanodiamonds evidently translocate into the bloodstream and/or other organs (Yuan et al 2010).…”
Section: Bio-compatibility Of Nanodiamondmentioning
confidence: 99%